Islamic bomb (United Kingdom : Journeyman Pictures, 2004)
Did America knowingly allow Pakistan to become the first Islamic nuclear state? Did they look the other way as Pakistan, Saudi Arabia and others connived to create the ultimate weapon in defence of Islam? Was America so desperate to defeat the Soviets that they quietly sanctioned a trade off, permitting the Muslim world to create a nuclear bomb in exchange for help driving the Russians from Afghanistan? A powerful and compelling indictment of US nuclear policy over the decades.
Keywords: Nuclear weapons -- Pakistan; Technology transfer -- Islamic countries